Behavioral changes in brain-injured critical care adults with different levels of consciousness during nociceptive stimulation: An observational study - Roulin, M.; Ramelet, Anne-Sylvie (Springer Verlag, 2014)
Purpose: The primary objective of this study was to describe the frequency of behaviors observed during rest, a non-nociceptive procedure, and a nociceptive procedure in brain-injured intensive care unit (ICU) patients with different levels of consciousness (LOC). Second, it examined the inter-rater reliability and discriminant and concurrent validity of the behavioral checklist used. Methods: The non-nociceptive procedure involved calling the patient and shaking his/her shoulder. The nociceptive procedure involved turning the patient. The frequency of behaviors was recorded using a behavioral checklist. Results: Patients with absence of movement, or stereotyped flexion or extension responses to a nociceptive stimulus displayed more behaviors during turning (median 5.5, range 0-14) than patients with localized responses (median 4, range 0-10) or able to self-report their pain (median 4, range 0-10). Face flushing, clenched teeth, clenched fist, and tremor were more frequent in patients with absence of movement, or stereotyped responses to a nociceptive stimulus. The reliability of the checklist was supported by a high intra-class correlation coefficient (0.77-0.92), and the internal consistency was acceptable in all three groups (KR 20, 0.71-0.85). Discriminant validity was supported as significantly more behaviors were observed during nociceptive stimulation than at rest. Concurrent validity was confirmed as checklist scores were correlated to the patients' self-reports of pain (r s = 0.53; 95 % CI 0.21-0.75). Conclusion: Brain-injured patients reacted significantly more during a nociceptive stimulus and the number of observed behaviors was higher in patients with a stereotyped response.